BIOETHICS AND BUDDHISM: THE HEART OF BUDDHIST ETHICS - Sivasai, Chintala Venkata (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The principle of applying thoughts and concepts in the real world to address biomedical problems is shared by both bioethics and Buddhism. Because philosophy is like a therapy that relieves human suffering, the Buddha stressed the usefulness of Buddhist ethical teachings. As a result, the Buddha avoided speculative metaphysics and placed an emphasis on practical ethics, which includes the eightfold way to end suffering in humans. Philosophical thought, which includes ethical thinking, is particularly intended to improve human existence by integrating its philosophical ideas into everyday activities. The formation of a Buddhist ethics that is truly universal and shamelessly normative is a larger process that needs to occur, and it is my hope that this book will just be a small part of it. Such an ethics is necessary in the world, both practically and philosophically. Theoretically, Buddhist ethics require application to a wide range of problems as well as a concise but universal explanation. More topics of public relevance exist than he has even able to touch on briefly in this book. These need to be discussed in much greater detail from a Buddhist perspective. The implementation of Buddhist principles in daily life is rather sporadic. Although there are some Buddhists who take ethics very seriously, they frequently only do so in regard to their own practice. This method promotes the idea that Buddhist ethics is primarily on personal purity, despite the fact that Buddhism's core values are in total opposition to such a focus. Buddhism should be tackling these issues if it is interested in the universal human problems.